ChemInform Abstract: Elemental Sulfur Disproportionation in the Redox Condensation Reaction Between o‐Halonitrobenzenes and Benzylamines. Issue 19 (May 2015) - Nguyen, Thanh Binh; Ermolenko, Ludmila; Retailleau, Pascal; Al‐Mourabit, Ali
Abstract: The reaction is applied in the synthesis of antitumor agent PMX 610 (IX).